Diferencial de juros e taxa de câmbio: um estudo empírico sobre o Brasil pós-plano real - Liu, John (2007)
This thesis examines the relationship between interest rates and exchange rate movements using the Uncovered Interest Rate Parity (UIP). Assuming rational expectations, we evaluated Brazilian data from Plano Real (July 1986) until August 2006. We found evidences that lead to reject UIP in the long run. Furthermore, we investigated the presence of UIP without the assumption of rational expectations. We used market surveys of future exchange, published at the Boletim Focus. We also found evidences that give no support to UIP hypothesis.